2022
DOI: 10.3389/fpsyt.2022.872331
|View full text |Cite
|
Sign up to set email alerts
|

A mental health survey among young front-line clinicians in high-risk areas during the COVID-19 sporadic epidemic in China

Abstract: BackgroundThe sporadic coronavirus disease (COVID-19) epidemic has placed enormous psychological stress on people, especially clinicians. The objective of this study was to examine depression, anxiety, quality of life (QOL), and related social psychological factors among young front-line clinicians in high-risk areas during the COVID-19 sporadic epidemic in China and to provide a reference for formulating reasonable countermeasures.MethodsIn this cross-sectional study, demographic information, COVID-19-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Infertile women were 16.1 times more likely to be depressed when their sleep quality is poor, showing a strong connection between poor sleep quality and depression. Previous investigations [ 27 29 ] implied that insomnia can increase the risk of depression or anxiety through impair emotional regulation, which supported our result. In addition, analysis of the PSQI scale revealed that 71.8% of patients suffered from subjective sleep disorders, but only 0.99% of patients used hypnotic drugs for sleep.…”
Section: Discussionsupporting
confidence: 92%
“…Infertile women were 16.1 times more likely to be depressed when their sleep quality is poor, showing a strong connection between poor sleep quality and depression. Previous investigations [ 27 29 ] implied that insomnia can increase the risk of depression or anxiety through impair emotional regulation, which supported our result. In addition, analysis of the PSQI scale revealed that 71.8% of patients suffered from subjective sleep disorders, but only 0.99% of patients used hypnotic drugs for sleep.…”
Section: Discussionsupporting
confidence: 92%
“…One or more areas of QoL were significantly impacted when disease severity and the degree of comorbidities were considered [ 22 ]. A study done in China among younger high-risk HCWs showed that QoL was significantly affected among HCWs working as frontline workers [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mental health conditions of adults after exposure to natural disasters have been most widely discussed by several journals. Many adults are involved as research subjects, namely breastfeeding mothers (Chen et al, 2020;Koyama et al, 2022), pregnant mother (Giarratano et al, 2019;He et al, 2021), caregiver (Li et al, 2021), and health experts (Suo et al, 2022). Several adults are a vulnerable group, according to the Inter-Agency Standing Committee organization Field (IASC) (2007), including pregnant women, single mothers, widows, and, in some cultures, unmarried adult women and teenage girls.…”
Section: Adultsmentioning
confidence: 99%
“…Furthermore, the smoking habit and lack of proper use of personal protective equipment among working adults can increase the risk of contact with pandemic survivors and, in the case of other disasters, the potential for injury. Supported by feelings of helplessness, the possibility of experiencing injury or death with physical health symptoms in adults can increase the risk of experiencing symptoms of anxiety, depression, stress and sleep problems, anxietydepression comorbidity, acute stress, and quality of life (QOL) (Li et al, 2021;Suo et al, 2022;Vujčić et al, 2021) Working women with low educational status are vulnerable to experiencing psychological problems (Li et al, 2021). Meanwhile, high socioeconomic status is significantly associated with low levels of depression, anxiety and stress (Vujčić et al, 2021).…”
Section: Adultsmentioning
confidence: 99%